The Anticaries Effect of a Food Extract (Shiitake) in a Short-Term Clinical Study - Lingström, Peter (Hindawi Publishing Corporation, 2012)
The main objective was to investigate whether low-molecular-weight fraction of edible mushroom shiitake extract (Lentinus edodes) possesses caries-preventive properties. The study was designed as a double-blind, three-leg, cross-over, randomized, controlled clinical trial carried out on two series of volunteers at the University of Gothenburg, and the Academic Centre for Dentistry Amsterdam. Volunteers rinsed twice daily with a solution containing low-molecular-weight fraction of edible mushroom, placebo (negative control without active ingredients), or Meridol (positive control, AmF-SnF(2)) for two weeks, with a two-week washout period between each rinsing period. Changes in the acidogenicity of dental plaque before and after a sucrose challenge, shifts in microbial composition, and plaque scores were determined. Frequent rinses with shiitake reduced the metabolic activity of dental plaque. No reduction of plaque scores and no inhibition of the production of organic acids in plaque was found. Minor differences in microbial composition between test sessions were found. To conclude, the results indicate that shiitake extract has anticariogenic potential, but not to the same extent as the positive control.